PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING KELAS V SDN 28 PADANG SARAI - Miranda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to improve social studies learning outcomes through a problem-based cooperative learning model for fifth grade students at SD Negeri 28 Padang Sarai for the 2022/2023 academic year. The research subjects for this class action were fifth grade students at SD Negeri 28 Padang Sarai for the 2022/2023 academic year as many as 32 students as recipients of the action, while for the subject of the action participants were social studies teacher class V as a teacher, colleagues as subjects who observed the learning process, The Principal as the subject of the data source. Methods of data collection is done through test techniques, observation and documentation. This Action Research was conducted in two cycles, each cycle consisting of: planning, action, observation and reflection. The results of this study indicate that the use of the problem-based learning model can improve social studies learning outcomes for fifth grade students at SD Negeri 28 Padang Sarai in the 2022/2023 academic year. This can be seen from the average score of social studies learning outcomes for students also increased, namely before the action of 70.19, in the first cycle of 76.38, and in the second cycle of 82.28. In addition, the percentage of student learning completeness, namely before the action was 34.38%, in cycle I was 68.75% and in cycle II was 96.88%.